Reflection learning innovation in the context of the lipa sabbe bunga caramming motif - Aras, Andi; Prahmana, Rully Charitas Indra; Zahrawati B, Fawziah; Buhaerah, Buhaerah; Busrah, Zulfiqar; Jumaisa, Jumaisa; Setialaksana, Wirawan (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
The low ability of students to understand and transform the concept of reflection to solve everyday problems is the main problem with learning mathematics because the implementation of learning mathematics is mechanical. Mathematics is taught by conveying formulas practically without linking them to students' daily activities. For this reason, this study aims to design a reflection learning trajectory in the context of the Lipa Sabbe Bunga Caramming motif as a starting point in learning to help students understand reflection material for solving everyday problems. The method used in this study is design research, which consists of three stages: preliminary design, design trials, and retrospective analysis. The subjects of this study were 23 students in class VIII-A of SMP Negeri 1 Tanasitolo. The instruments used in this study were student activity sheets (LAS), learning achievement tests, and interview guidelines. Student activity data during learning were analyzed retrospectively, and learning outcomes data were analyzed descriptively. The results of this study found that the learning trajectory of transformation geometry using the context of the lipa sabbe bunga caramming motif has four learning stages: (1) informal; (2) modes of; (3) modes of; and (4) formal. The learning stages can easily increase students' understanding of the concept of reflection. In the learning process, mathematical concepts are connected with daily habits, so students are enthusiastic and active in the learning process. This learning trajectory can assist teachers in optimizing learning so that students can easily understand the concept of reflection, equip them with critical thinking skills, and shape their character (cooperation, empathy, respect for others, awareness of social problems, a social spirit, and responsibility).